Strategies of Raw Material Diversification in Management of Resource Supplies of Oil Extraction Companies - Irina Petrovna BOGOMOLOVA; Nataliya Mitrofanovna SHATOHINA; Lyudmila Timofeevna TRINEEVA; Sergey Anatolevich LOSKUTOV; Irina Evgenievna USTYUGOVA (Communications of International Proceedings, 2020)
The urgency of this research is predetermined by a significant role of the food industry in securing food independence of the Russian Federation, stiffer competition on the local and foreign markets, lower effectiveness of resource use at oil extraction companies. The objective of the research is to adapt the raw material diversification mechanisms to industry specifics of managing raw materials supplies at oil extraction companies to widen the production range without infringing the interests of plant growing companies, which specialize in oil seeds, and vegetable processing companies. Our article dwells on the scientific and methodological basis of raw material diversification of oil extraction companies and trends of raw materials provision of the Russian Federation’s oil extraction enterprises, which became the basis of our recommendations to improve company management when implementing a raw material diversification strategy. Insufficient knowledge of organizational and economic issues of raw materials diversification and scientific and practical importance of raw materials diversification in managing food company supplies predetermined the novelty of our research.
Keywords: Raw Material Diversification; Processing Industry; The Agro-Industrial Complex; Efficient Use Of Raw Materials; Raw Materials Supplies.